2009
DOI: 10.1111/j.1365-2036.2008.03897.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in patients on long‐term proton pump inhibitors: prevalence and predictors

Abstract: SUMMARY BackgroundSymptom control in primary care patients on long-term proton pump inhibitor (PPI) treatment is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
2
20
0
1
Order By: Relevance
“…Th is is a simple fi ve-item questionnaire that evaluates anxiety and depression, pain or discomfort, self-care, impact on usual activities, and mobility. It has been used in previous surveys of GERD in both primary ( 22,23 ) and secondary care ( 23 ), and has been correlated to refl ux symptom severity. To our knowledge, this is the fi rst randomized controlled trial to evaluate GERD pharmacological therapy that has used the EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…Th is is a simple fi ve-item questionnaire that evaluates anxiety and depression, pain or discomfort, self-care, impact on usual activities, and mobility. It has been used in previous surveys of GERD in both primary ( 22,23 ) and secondary care ( 23 ), and has been correlated to refl ux symptom severity. To our knowledge, this is the fi rst randomized controlled trial to evaluate GERD pharmacological therapy that has used the EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional survey of 726 patients on long-term PPIs (39% GERD) found that reflux symptoms persisted in 59% of patients [46]. Our recent meta-analysis of symptomatic GERD patients found that in about two-thirds of patients, reflux symptoms are not adequately controlled after the first dose of a PPI, and nearly 50% patients still suffer symptoms 3 days later [47].…”
Section: Unmet Need Of Current Delayed Release-proton Pump Inhibitorsmentioning
confidence: 96%
“…Ðåçóëüòàòû èññëåäîâàíèÿ ñðàâíèòåëü-íîé àêòèâíîñòè ðàçëè÷íûõ ÈÏÍ (ýçîìåïðàçîë, ëàí-ñîïðàçîë, ïàíòîïðàçîë, ðàáåïðàçîë) äîñòàòî÷íî ïðîòè-âîðå÷èâû [23]. Õîòÿ ÈÏÍ ÿâëÿþòñÿ ñàìûìè óñïåøíûìè èíãèáèòîðàìè êèñëîòîïðîäóêöèè, ó 59 % áîëüíûõ ÃÝÐÁ íà ôîíå äîëãîñðî÷íîé òåðàïèè ÈÏÍ íå èñ÷åçàþò ñèìïòîìû ðåôëþêñà [42]. Ïàöèåíòû ñ ÍÝÐÁ äåìîíñòðèðóþò ñàìóþ ìåäëåííóþ ñêîðîñòü ðàçâèòèÿ îòâåòà íà ÈÏÍ, è ýòîò îòâåò ñîñòàâëÿåò ëèøü îêîëî 50 -60 %.…”
Section: êëèíè÷åñêàÿ ýôôåêòèâíîñòüunclassified